INFLUENCE OF THE MIX OF PRICE, PLACE, PROCESS ON GUEST SATISFACTION OF GRAND ORRI BERASTAGI HOTEL IN 2021 - Herikson Tampubolon (International Journal of Economic, Technology and Social Sciences (Injects), 2021)
The purpose of the research is to find out the influence of Price, Place, Process on Guest satisfaction at Grand Orri Berastagi Hotel. The type of research used is a quantitative approach. The sample used as many as 95 hotel guests as respondents. Data collection techniques using questionnaires. Data analysis techniques use validity test, reliability test, normality test, heterokedasity test, multiconearity test, simple liner regression test, partial test (t test), model test (F test), and determination coefficient test. The results showed that Price, Place, Process had a significant effect on guest satisfaction.